2021
DOI: 10.1080/17512433.2021.1901578
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nrf2 signaling pathway by natural and synthetic chalcones: a therapeutic road map for oxidative stress

Abstract: Introduction:Nuclear factor erythroid 2-related factor 2 (Nrf2) signaling pathway plays a key role in diverse gene expressions responsible for protection against oxidative stress and xenobiotics. Chalcones with a common chemical scaffold of 1,3-diaryl-2propen-1-one, are abundantly present in nature with a wide variety of pharmacological properties. This review will discuss the interactions of natural and synthetic chalcones with Nrf2 signaling. Areas covered:Chalcones are reportedly found to activate Nrf2 sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 163 publications
0
33
0
Order By: Relevance
“…There has been an increasing number of publications that detail the relationship between chalcones and Nrf2, with several studies reporting the ability of chalcones to induce Nrf2. The ability of synthetic and natural chalcones to activate the Nrf2 signaling pathway was reviewed recently [15]. Ajiboye et al [16] reported that natural chalcones lophirones B (12) and C (13) could induce Nrf2 (Figure 3).…”
Section: Activation Of Nuclear Factor-erythroid 2 P45 Subunit-related Factor 2 Pathway and Cellular Defence Genesmentioning
confidence: 99%
“…There has been an increasing number of publications that detail the relationship between chalcones and Nrf2, with several studies reporting the ability of chalcones to induce Nrf2. The ability of synthetic and natural chalcones to activate the Nrf2 signaling pathway was reviewed recently [15]. Ajiboye et al [16] reported that natural chalcones lophirones B (12) and C (13) could induce Nrf2 (Figure 3).…”
Section: Activation Of Nuclear Factor-erythroid 2 P45 Subunit-related Factor 2 Pathway and Cellular Defence Genesmentioning
confidence: 99%
“…NRF2 is positively regulated by three MAP kinases, ERK, JNK, and p38, and the protein kinase (PKR)-like endoplasmic reticulum kinase (PERK) [ 15 ]. NRF2/ARE signaling has been considered as a promising target against oxidative stress-mediated diseases like diabetes, fibrosis, neurotoxicity, and cancer [ 16 ]. In this review, we will focus on the NRF2/ARE signaling pathway and its role in oxidative stress-mediated diseases.…”
Section: Nrf2-antioxidant Defense System Pathwaymentioning
confidence: 99%
“…In another model of inhibition of oxidative stress, GPETAFLR, a lupin-originated octapeptide, was demonstrated to increase cell viability and improve GSH synthesis, while suppressing ROS generation in retinal pigment epithelium cells [ 28 ]. This finding suggests that consumption of lupin-rich diet will provide health benefits such as delaying the onset of AMD, a condition that has been shown to be associated with free radical attack on ocular tissues, compromising the blood-retinal barrier that results in initiation and progression of ADM [ 82 , 83 , 84 ]. Taken together, these reports on the antioxidant properties of LDPs strongly position LDPs as candidates for functional food developments for diseases with oxidative stress etiology.…”
Section: Biological Activities Of Ldpsmentioning
confidence: 99%